2020
DOI: 10.21608/ejhc.2020.147928
|View full text |Cite
|
Sign up to set email alerts
|

Learning Organization and Its Influence on Organization’ Resilience and Creativity in Mansoura Oncology Center

Abstract: Background: Nowadays, all organizations as response to challenges strive to build strong internal and external cooperation through Learning and resilience. These strong alliances and cooperation enable all employees to create new ideas to face these challenges through enhancing and encouraging capabilities of learning & creativity. Aim: The purpose of this study was to assess the influence of learning organization on organization resilience and creativity in Mansoura Oncology Center. Design: Descriptive correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…While less than one fifth of them had low level of resilience. This result on agreement with (Elsayed and Abdel-Ghani 2020), who examined The Learning organization and Its influence on organization' resilience and creativity in Mansoura Oncology Center they assessed the level of organizational resilience in Mansoura Oncology Center, and they found that the resilience level was high. The previous findings were dissimilar to the study of (Gabaisen et al 2023), The who examined The Influence of Faculty Members' Resiliency and Organizational Citizenship Behavior as Predictors of Teaching Performance and reported that the resilience level was low.…”
Section: Discussionsupporting
confidence: 83%
“…While less than one fifth of them had low level of resilience. This result on agreement with (Elsayed and Abdel-Ghani 2020), who examined The Learning organization and Its influence on organization' resilience and creativity in Mansoura Oncology Center they assessed the level of organizational resilience in Mansoura Oncology Center, and they found that the resilience level was high. The previous findings were dissimilar to the study of (Gabaisen et al 2023), The who examined The Influence of Faculty Members' Resiliency and Organizational Citizenship Behavior as Predictors of Teaching Performance and reported that the resilience level was low.…”
Section: Discussionsupporting
confidence: 83%
“…Creativity is vital for an organization to support development and keep in touch with the latest trends in the industry [50]. Employee creativity has been examined with other elements such as organizational learning [51] and perceived organizational support [52]. Organizations can play a fundamental role in promoting employee creativity [53].…”
Section: Empirical Review 231 Knowledge Worker and Employee Creativitymentioning
confidence: 99%
“…The organization can instill a process of creativity by challenging employees to look beyond what is known, which will eventually lead to innovative changes [53]. Elsayed and Abdel-ghani [51] found a positive and significant correlation between learning organizations and employee creativity as employees' creativity increases in learning organizations. Organization's leaders are willing to have employees who are self-motivated to be creative [62].…”
Section: Empirical Review 231 Knowledge Worker and Employee Creativitymentioning
confidence: 99%
“…Meanwhile, Elsayed and Abdel-ghani (2020) in addition to resilience, as an essential ability of an organization to expect, design, respond and adapt to progressive alteration and unexpected disturbances, also highlight the ability of creativity. Learning organizations are constantly looking for creative solutions which increase their ability to successfully adapt in the context of COVID-19 pandemic uncertainty.…”
Section: Introductionmentioning
confidence: 99%